Impact of Tropical Cyclones on Pelagic Sargassum. Issue 6 (15th March 2022) - Sosa‐Gutierrez, Rosmery; Jouanno, Julien; Berline, Leo; Descloitres, Jacques; Chevalier, Cristèle
Abstract: The strong proliferation of holopelagic Sargassum in the Tropical Atlantic from 2011, raises many questions on the environmental factors controlling their growth and decay at interannual, seasonal, and intraseasonal scales. In this work, we specifically investigate the response of the Sargassum aggregations to high wind events such as those found in Tropical Cyclones (TCs). The evolution of Sargassum coverage obtained from MODIS observations in the north tropical Atlantic Ocean (from 0 to 30°N and from 0 to 100°W) was analyzed under 86 historical paths of TCs and tropical storms from 2011 to 2020 that crossed Sargassum aggregations. Our results show on average a 40% drop in Sargassum coverage under TC trajectories, which can exceed 60% for the most intense TCs. We associate this drop with a sinking of Sargassum toward the deep ocean. Our estimates suggest that TCs contribute to the seasonal decay of Sargassum biomass from August to November. Plain Language Summary: The massive development of holopelagic Sargassum spp. In the north tropical Atlantic Ocean from 2011 to present causes annual stranding in millions of tons on the coasts of the Tropical Atlantic. The causes for this proliferation are still uncertain and may involve a combination of environmental factors. Both in areas where the presence of Sargassum is known for a long time, such as the Sargasso Sea and the Gulf of Mexico, and in new areas of proliferation, such as the Caribbean and the Central Atlantic, Sargassum are subject to Tropical Cyclones (TCs). In this work, we specifically investigate the response of the Sargassum aggregations to high wind events such as those found in TCs. By combining satellite observations and TC tracks from 2011 to 2020, this study shows that high winds produce massive decrease of Sargassum coverage as detected by satellite, which can reach 60% for the most energetic TCs. So TCs may contribute to shape the seasonal cycle of Sargassum coverage, and in particular its decay from July to October. Key Points: Tropical cyclones occur in the region of massive proliferation of Sargassum since 2011 High winds in tropical cyclones induce decrease of Sargassum coverage No recovery of Sargassum after cyclone crossing